Phenomenological Study: The Impact of Impulsive Shopping Tendency on Online Shopping Behavior of Students at Indragiri Tembilahan Islamic University - Muchlis, Muchlis; Wijayanto , Gatot (ProBisnis : Jurnal Manajemen, 2025)
This qualitative study in-depth investigates the online impulsive shopping experience among students at Indragiri Tembilahan Islamic University through a phenomenological approach. Data were collected through in-depth interviews with 20 purposively selected participants. The findings revealed that: (1) Emotional factors (stress, boredom) and external stimuli (targeted advertising, flash sale discounts) are the main triggers; (2) Behavioral impacts include disruptions in personal financial management and changes in consumption patterns; (3) The campus environment acts as a moderating factor through peer influence. This study provides theoretical contributions to the literature on digital consumer behavior in the context of Indonesian higher education as well as practical implications for e-commerce platform developers and campus policymakers.